Antidepressant use and colorectal cancer morbidity and mortality: A dose-response meta analysis. Issue 22 (29th May 2020) - Chen, Lin; Li, Xun; Li, Chengbin; Zou, Chuanxin
Abstract : Abstract: The risk of colorectal cancer associated to antidepressant use remains unclear. The purpose of this meta-analysis was to investigate the risk of colorectal cancer associated to antidepressant use. Medline, Embase, Web of Science, and Cochrane Database were accessed from the dates of their establishment to October 2018, to collect study of antidepressant use and colorectal cancer morbidity and mortality. Then a meta-analysis was conducted using Stata 12.0 software. A total of 11 publications involving 109, 506 participants were included. The meta-analysis showed that antidepressant use was not associated with colorectal cancer morbidity (relevant risk (RR): 0.97; 95% confidence interval (CI): 0.94–1.01) and mortality (RR: 1.08; 95% CI: 0.99–1.17). Subgroup analysis showed selective serotonin reuptake inhibitor (RR: 0.99; 95% CI: 0.96–1.03) or serotonin norepinephrine reuptake inhibitor (RR: 1.04; 95% CI: 0.86–1.26) were not associated with colorectal cancer risk; however, TCA was associated with colorectal cancer risk decrement (RR: 0.92; 95% CI: 0.87–0.98). Furthermore, the results also showed that antidepressant use was not associated with colorectal cancer risk in Europe and North America (RR: 0.97; 95% CI: 0.92–1.02) and Asia (RR: 1.00; 95% CI: 0.95–1.26). Additionally, a dose-response showed per 1 year of duration of antidepressant use incremental increase was not associated with colorectal cancer risk (RR: 0.96; 95% CI: 0.87–1.09). Evidence suggests that antidepressant use was not associated with colorectal cancer morbidity and mortality. The cumulative duration of antidepressant use did not utilized played critical roles. Abstract : Supplemental Digital Content is available in the text